2014
DOI: 10.1088/1367-2630/16/7/073001
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of slow electrostatic shock into a plasma shock mediated by electrostatic turbulence

Abstract: The collision of two plasma clouds at a speed that exceeds the ion acoustic speed can result in the formation of shocks. This phenomenon is observed not only in astrophysical scenarios, such as the propagation of supernova remnant (SNR) blast shells into the interstellar medium, but also in laboratory-based laserplasma experiments. These experiments and supporting simulations are thus seen as an attractive platform for small-scale reproduction and study of astrophysical shocks in the laboratory. We model two p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 72 publications
3
21
0
Order By: Relevance
“…This instability is known to destroy planar double layers and electrostatic shocks (Karimabadi et al 1991;Kato & Takabe 2010;Dieckmann et al 2015a) and here we have shown that it also affects the nonplanar ones.…”
Section: Discussionsupporting
confidence: 50%
“…This instability is known to destroy planar double layers and electrostatic shocks (Karimabadi et al 1991;Kato & Takabe 2010;Dieckmann et al 2015a) and here we have shown that it also affects the nonplanar ones.…”
Section: Discussionsupporting
confidence: 50%
“…Simulations have shown that drift instabilities and electrostatic turbulence can in some cases suppress the growth of a magnetosonic wave. 3 As we go to higher flow speeds, the plasma shocks become magnetized by filamentation instabilities. [4][5][6][7] We consider here shocks, which develop in an initially unmagnetized and collisionless plasma.…”
Section: Introductionmentioning
confidence: 99%
“…17 Obliquely propagating ion acoustic waves grow in the foreshock region and modulate the incoming upstream ions. The plasma shock is either transformed into a shock with a broad transition layer 3 or it is destroyed by the inflowing turbulent plasma. 16 Previous simulation studies have addressed the evolution of (quasi-)planar plasma shocks.…”
Section: Introductionmentioning
confidence: 99%
“…The LH and electron cyclotron drift instabilities will drive waves with wavevectors that are aligned with the electron drift speed. 31,40,41 These drift instabilities are thus suppressed by the one-dimensional simulation geometry.…”
Section: Phys Plasmas 23 062111 (2016)mentioning
confidence: 99%
“…4,6,31 The LH shock is modified by the magnetic field it is piling up as it expands into the upstream region. The magnetic pressure gradient force it exerts on the ambient ions in the upstream region is pre-accelerating them, which reduces the ion velocity change at the shock to a value that is comparable to or below the phase speed of the LH wave.…”
Section: Introductionmentioning
confidence: 99%